2014
DOI: 10.1111/trf.12712
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of stored blood impairs host defenses against Gram‐negative pathogens in mice

Abstract: BACKGROUND Although human red blood cell (RBC) units may be refrigerator stored for up to 42 days, transfusion of older RBCs acutely delivers a large bolus of iron to mononuclear phagocytes. Similarly, iron dextran circulates in plasma for hours to days and is progressively cleared by mononuclear phagocytes, which return iron to plasma. Finally, malaria infection continuously delivers iron to macrophages by intra- and extravascular hemolysis. Studies suggest that iron administration increases infectious risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 48 publications
(65 reference statements)
0
58
0
2
Order By: Relevance
“…Laboratory findings have shown that longer stored RBCs are more actively phagocytosed [105][106][107] and thereby could possibly induce immunosuppressive effects, including increased susceptibility to infection [88,105]. Prolonged storage renders RBCs more susceptible to mechanical fragility and altered membrane permeability that can increase intravascular hemolysis [108,109].…”
Section: Red Blood Cell Storage Lesion and Potential Consequences Formentioning
confidence: 98%
See 1 more Smart Citation
“…Laboratory findings have shown that longer stored RBCs are more actively phagocytosed [105][106][107] and thereby could possibly induce immunosuppressive effects, including increased susceptibility to infection [88,105]. Prolonged storage renders RBCs more susceptible to mechanical fragility and altered membrane permeability that can increase intravascular hemolysis [108,109].…”
Section: Red Blood Cell Storage Lesion and Potential Consequences Formentioning
confidence: 98%
“…Interest in the possible intersection of storage-related RBC changes and trauma has sparked new laboratory-based research to investigate the potential immune and vascular effects resulting from transfusion of longer stored RBCs in critically ill patients [83,84]. A "two-insult" model of posttransfusion injury has been suggested by several investigators as a working hypothesis [85][86][87][88]. This model proposes that the first insult is the patient's underlying immunomodulatory condition (eg, trauma injury) that primes the patient's immune-vascular system and a second inflammatory insult triggers full-scale activation that broadens the injurious state.…”
Section: Red Blood Cell Storage Lesion and Potential Consequences Formentioning
confidence: 99%
“…Thus, transfusions of fresh RBCs produce no laboratory evidence of hemolysis, whereas transfusions after longer storage durations result in substantial clearance of storage-damaged RBCs, inducing increased levels of circulating bilirubin, iron, and non-transferrin-bound iron [10]. This circulating non-transferrin-bound iron (e.g., iron not bound to transferrin, the physiologic iron transporter) enhances bacterial growth in plasma in vitro [10] and may enhance bacterial infection in vivo [16]. Furthermore, hemolysis is associated with poorer survival in septic patients [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…51 Hemolysis and free iron have been associated with multiple complications of transfusions and diseases such as sickle cell anemia. 52,53 Authors did not, however, report these aspects of blood processing consistently or completely enough to allow for further analyses.…”
Section: Strengths and Concerns/limitationsmentioning
confidence: 99%